The Effect of ''Care'' and ''Protection'' Characteristics of Father-Daughter Relationship in Childhood and Adolescent Years of Girls, on Women's Self-Esteem and Women's Femininity ans Masculinity/Psychology Research Project: Completed in Fulfillment of the Degree of Bachelor of Science (HONOURS) in Applied Psychology - Farasopoulou Athanasia; Thomas, George B. 1914-2006 (George Brinton) (2019)
Title, Author Declaration, Acknowledgements, Table of Contents, Abstract, Introduction, Rationale, Hypotheses, Method, Design, Participants, Materials, Procedure, Analytic Strategy, Results, Discussion, References, Appendices.